THE INFLUENCE OF HEALTH PROFESSIONALS ON THE CHOICE TO USE SIGN LANGUAGE - Lima, Layane Rocha de; Silva, Maria Clara Souza Rodrigues da; Firmino, Camila Correia; Melo, Givânya Bezerra de; Lisbôa, Gabrielle Leite Pacheco (Cogitare Enfermagem, 2022)
Objective: to understand how the conduct of health professional’s influences (or does not influence) parents and/or guardians in choosing the use of sign language after the diagnosis of deafness. Method: descriptive study of qualitative approach carried out with parents/guardians of deaf children and adolescents. Data were collected through interviews, conducted in October and November 2021 in the city of Maceió/AL - BR, data were analyzed according to Bardin. Results: sign language is not the first alternative suggested to parents as a form of communication with deaf children, since professionals prioritize the use of hearing aids and cochlear implant, although often its effectiveness is questioned. Conclusion: the study contributes to expand the literature on the theme, which is still scarce, making it possible to discuss the privileged role that the health professional must positively influence the lives of deaf individuals and their families.